Air Permeability and Water Vapor Resistance of Differently Finished Cotton and Cotton/Elastane Single Jersey Knitted Fabrics - Aleksandra Ivanovska; Mirjana Reljic; Mirjana Kostic; Koviljka Asanovic; Biljana Mangovska (Journal of Natural Fibers, 2022)
This study investigates the knitted fabrics’ air permeability and water vapor resistance as complex phenomena of the interaction between the fiber nature, fabric structural characteristics and, different wet processes. Bleaching and dyeing together with the content of elastane are the main factors determining fabric structural characteristics. 100% cotton fabrics have a higher intensity of warm/cool feeling since they have higher air permeability than elastane containing fabrics. The air permeability and water vapor resistance of elastane containing fabrics decreased after the wet processes, whereby the bleached knitted fabrics showed higher air permeability and lower water vapor resistance than dyed. Decreased air permeability and increased water vapor resistance of softened elastane containing fabrics are governed by the cationic softener pick-up mechanism. Namely, the cationic softener is deposited on the yarns’ surfaces; its hydrophobic carbon ends repel from each other. This acts as a barrier for air which contributes to an increase in the fabric water vapor resistance. The softened dyed knitted fabrics have lower air permeability and slightly higher water vapor resistance than softened bleached fabrics which may be attributed to the interaction between reactive dyestuff and cationic softener. The comfort properties quality of finished knitted fabrics decreased with elastane incorporation and with softening.